2013
DOI: 10.1007/s10709-013-9733-6
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal DNA is active in different B chromosome variants of the grasshopper Eyprepocnemis plorans

Abstract: B chromosomes are considered to be genetically inert elements. However, some of them are able to show nucleolus organizer region (NOR) activity, as detected by both cytological and molecular means. The grasshopper Eyprepocnemis plorans shows a B chromosome polymorphism characterized by the existence of many B variants. One of them, B24, shows NOR activity in about half of B-carrying males in the Torrox population. Molecular data have suggested the recent origin for B chromosomes in this species, and on this ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Teruel et al [21] reported the presence of H3 and H4 histone sequences with the same putative amino acid sequences in the L. migratoria B chromosomes as those obtained from 0B genomic DNA indicating that they are potentially active. Ruiz-Estévez et al [76] detected B-derived rRNA sequences in grasshopper Eyprepocnemis plorans confirming that B sequences are potentially active and can contribute to the host genome functions. Pseudogenic sequences of B chromosomes in rye are expressed and have potential to regulate the expression of A-located genes [40].…”
Section: Discussionmentioning
confidence: 97%
“…Teruel et al [21] reported the presence of H3 and H4 histone sequences with the same putative amino acid sequences in the L. migratoria B chromosomes as those obtained from 0B genomic DNA indicating that they are potentially active. Ruiz-Estévez et al [76] detected B-derived rRNA sequences in grasshopper Eyprepocnemis plorans confirming that B sequences are potentially active and can contribute to the host genome functions. Pseudogenic sequences of B chromosomes in rye are expressed and have potential to regulate the expression of A-located genes [40].…”
Section: Discussionmentioning
confidence: 97%
“…They usually consist of highly repetitive DNA sequences, such as ribosomal DNA, satellite DNA, and mobile elements [1], [2], [3], while examples of B chromosomes carrying coding sequences [4], [5], [6], [7], functional ribosomal DNA [8], [9], and influencing sex determination [10] have recently been reported. In some cases, DNA sequences in the B chromosomes resemble those in the A chromosomes of the same genome (intraspecific origin) whereas, in others, they are more similar to DNA sequences in the genome of a relative species (interspecific origin) [11].…”
Section: Introductionmentioning
confidence: 99%
“…B chromosomes of E. plorans are able to transcribe their rDNA and organize a nucleolus18, although this occurs only in a minority of males from most populations33, and the rRNA contribution by the B to total rRNA is insignificant compared to that from A chromosomes34, suggesting that B chromosomes in this species are highly repressed. Here we analyze the possible presence of protein-coding genes in the B chromosome of this species by means of NGS analysis of 0B and 4B male genomes and their mapping against the coding sequence (CDS) regions of a de novo assembled transcriptome built with all the reads obtained from 0B and 1B female RNAs.…”
mentioning
confidence: 95%